Theoretical-methodological assumptions and praxis of empirical investigation: Place, participant observation, tourism and sex workers in Havana - da Gama, Helio Fernando Lôbo Nogueira (Seven Editora, 2023)
The objective is to present the theoretical basis and describe the empirical practice of the research methodology on a social impact of tourism in the havanero place, the sex workers, criminalized as prostitutes/jineteras. The epistemology of Husserl's phenomenology and Kosik's dialectics give rise to a participant observation as a methodology of insertion in the social fabric as a "tourist"/researcher, in search of the meanings that are established in the "unauthorized" approaches of autochthonous people and the relationship between essence/totality of the phenomenon. The essential hypothesis or intuition: such a path in the sociological investigation of the social phenomenon tourism is legitimate as a theoretical-methodological choice. It enhances its continuous development as a strategy of approximation and inquiry in any geopolitical and socioeconomic contexts. The relationship between the concept of place and participant observation as a consistent research method and technique is essential. In a historical and theoretical perspective, I trace the geopolitical, economic and social conjuncture in which Cuba opened itself as an international tourist destination, scenarios of empirical investigative praxis. Ethnographic data collected with phenomenological inspiration, especially on the meaning of the social actors who granted me in-depth interviews, are reported from their narratives. As the dialectical method continues when the phenomenological ends, I contextualized them historically and politically in search of inferring generalizations. I make the insertion of data of the current conjuncture, seeking to reinforce the need for the development of the methodology undertaken in Sociology of Tourism.DOI:https://doi.org/10.56238/alookdevelopv1-073